Enhanced toughness in ceramic-reinforced polymer composites with herringbone architectures. (1st March 2021) - Zando, Robert B.; Mesgarnejad, Ataollah; Pan, Chunzhou; Shefelbine, Sandra J.; Karma, Alain; Erb, Randall M.
Abstract: Crack deflection is often used as evidence of substantive fracture toughness in both natural and synthetic composites. The associated microstructures of these tough composites are often highly anisotropic, exhibiting both easy and hard directions for crack propagation. Cracks generally deflect away from hard directions to propagate instead in easy directions tying the overall fracture toughness to its weak axis. Instead, enhanced fracture toughness can be realized when cracks are forced to propagate along the hard directions. Recent advances in composite manufacturing including 3D magnetic printing have enabled the creation of detailed microstructures that can locally tune the fracture toughness anisotropy. In this work, we investigate a family of architectures reminiscent of a herringbone pattern, in which propagating cracks are effectively trapped along the spine between two regions. Along this spine, a crack can be inhibited from deflecting and forced to propagate along a relatively hard direction, resulting in a significant boost in initial and overall fracture toughness. We expand these realizations to generate beautiful herringbone mosaics that exhibit isotropic and enhanced fracture toughness. We have approached this problem with both numerical and experimental modalities to systematically test and characterize this new class of composite architectures. Graphical abstract: Image 1